Financial aid, debt management, and socioeconomic outcomes: Post-college effects of merit-based aid - Judith E. Scott-Clayton; Basit Zafar (Federal Reserve Bank of New York, 2016)
Prior research has demonstrated that financial aid can influence both college enrollments and completions, but less is known about its post-college consequences. Even for students whose attainment is unaffected, financial aid may affect post-college outcomes via reductions in both time to degree and debt at graduation. We utilize two complementary quasi-experimental strategies to identify causal effects of the WV PROMISE scholarship, a broad-based state merit aid program, up to ten years post-college-entry. This study is the first to link college transcripts and financial aid information to credit bureau data later in life, enabling us to examine important outcomes that have not previously been examined, including homeownership, neighborhood characteristics, and financial management (credit risk scores, defaults, and delinquencies). We find that even as graduation impacts fade out over time, impacts on other outcomes emerge: scholarship recipients are more likely to earn a graduate degree, more likely to own a home and live in higher-income neighborhoods, less likely to have adverse credit outcomes, and more likely to be in better financial health than similar students who did not receive scholarships.
Keywords: I22; I26; J24; 330; merit aid; debt management; financial health